2020
DOI: 10.14807/ijmp.v11i9.1430
|View full text |Cite
|
Sign up to set email alerts
|

Accounting trends in the modern world

Abstract: The purpose of the article is to determine the current directions and future trends in the development of accounting. The conclusions made on the basis of research materials, surveys, reports of reputable international and professional accounting organizations. Synthesis and analysis reveal that some trends and drivers among analyzed will be more significant (such as globalization of business and the profession; spread of digital technologies; expectations of business and professional accountants) than others … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…One clear implication of this conundrum is that accountants and accounting students will need to have strong transversal skills, including soft skills such as self-regulation, communication, and teamwork [11], as well as IT proficiency [12][13][14] and technological skills such as automated systems and accounting information systems (AIS), which allow for the collection, treatment, and dissemination of financial/accounting information [15] and are a more efficient and efficacious response to clients' needs, with faster and bettersupported responses [16,17].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…One clear implication of this conundrum is that accountants and accounting students will need to have strong transversal skills, including soft skills such as self-regulation, communication, and teamwork [11], as well as IT proficiency [12][13][14] and technological skills such as automated systems and accounting information systems (AIS), which allow for the collection, treatment, and dissemination of financial/accounting information [15] and are a more efficient and efficacious response to clients' needs, with faster and bettersupported responses [16,17].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Additionally, of the 103 studies selected and published between 2018 and 2021 it was found that accounting and its professionals, were addressed in six articles and they are: 1) Lin and Hwang ( 2021 ) presented an empirical study (quantitative approach) on how accountants manage knowledge sharing, information management and the psychological factors associated with this in the pre-pandemic and pandemic periods, concluding that information management skills and perceived image have a positive association with knowledge sharing behaviour, while reciprocity and knowledge power loss do not play a relevant role in knowledge sharing intentions; also suggest that accountants need to be increasingly resilient; 2) Feeney and Pierce ( 2018 ) empirically demonstrated (qualitative approach) that accounting is an enabler of innovation and creativity; 3) Dechawatanapaisal ( 2020 ) obtained a sample of 1137 accountants (questionnaire) to develop a model to examine whether work significantly influences career satisfaction through job integration, where the results obtained showed that the direct relationship existing between job meaning and satisfaction are measured by integration; 4) Melnyk et al ( 2020 ) identified the current and future directions in the development of accounting; 5) Faituša et al ( 2020 ) evaluated accounting outsourcing in Latvia and Lithuania (inductive and deductive method) and identified the personal, professional and social characteristics of certified accountants; 6) Mihai et al ( 2020 ) investigated how the pandemic forced accountants to make a heavy investment in their work (workload), which generated stressful situations, but with a positive balance in the relationship with the family. In short, empirical studies on work stress in accounting professionals are minute, which opens space to argue that this is a fertile topic for research and to justify the essence of this study presented here as a starting point.…”
Section: Scientific Mappingmentioning
confidence: 99%
“…Accounting professionals with higher abilities and experience have a more noteworthy impact on the basic leadership procedures of a business (Ramli et al, 2013;Tout et al, 2014). When it comes to determining the quality of accounting services provided to SMEs, the understanding of accounting, the skill and integrity of the accountant, as well as the independence demonstrated by the accountant are all crucial factors (Blackburn et al, 2018;Melnyk et al, 2020). The research, therefore, aimed to investigate the effects of an accountant's competence and independence on accountancy service delivery in SMEs in Ghana.…”
Section: Introductionmentioning
confidence: 99%